Optical quality changes of the eye during peak SARS-CoV-2 pandemic in young adults - He Tian; Qian Fan; Wenjing Gao; Yan Wang (Heliyon)
Introduction: To determine whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection affects corneal morphology and optical quality. Methods: In this cross-sectional study, ophthalmological indicators were examined during the peak of SARS-CoV-2 infection after adjusting for public health control measures. Participants were divided into control (remained uninfected), A (infected during follow-up), and B (infected prior to the first consultation) groups. Effects of varying SARS-CoV-2 infection levels were determined using reverse transcription polymerase chain reaction. Changes in corneal morphology, backscatter, and aberrations were measured. Corneal parameters, such as flat keratometry, steep keratometry, and surface variance, vertical asymmetry, height asymmetry, and height decentration indices were considered. Results: Overall, 110 participants (208 eyes, 42.7 % male; age 17–31 years) were enrolled. Eighteen (16.3 %) were infection-free during the outbreak with unchanged corneal morphology, backscatter, and aberration. In group A, 34.73 ± 9.30 days after infection, the backscatter of the anterior corneal layer and central layer (both p = 0.000) decreased. Total low-order aberration, defocus, horizontal coma, and spherical aberration of the cornea increased (p < 0.05), while corneal morphology after infection did not change (p > 0.05). In group B, a decrease in backscattering in the corneal middle layer and an increase in horizontal coma (p < 0.05) were noted. Conclusion: Backscattering of the anterior and intermediate layers of the cornea decreased and corneal aberrations increased after SARS-CoV-2 infection, which affected corneal optical quality. However, corneal morphology and thickness remained unchanged. Ophthalmological indicators and optical quality should be monitored during SARS-CoV-2 infection.